2020
DOI: 10.3389/fpubh.2020.00096
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Children Living With HIV on Art in Zambia: A 13-Years Retrospective Cohort Analysis

Abstract: Background: Research conducted before the introduction of anti-retroviral therapy (ART), showed that the majority of children living with HIV (CLHIV) would die before their second birthday. In Zambia, ART was rolled out to the public health system in 2004 with subsequent improved survival in CLHIV. However, the survival rates of CLHIV on ART in Zambia since 2004 have not been extensively documented. We assessed survival experiences and the factors associated with survival in CLHIV on ART in Zambia. Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Published data indicate that some adolescents and young adults living with HIV may die within the first year of ART initiation [ 10 , 11 , 12 , 13 ]. The predictors of mortality among adolescents and young adults living with HIV are not uniform across studies [ 7 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Published data indicate that some adolescents and young adults living with HIV may die within the first year of ART initiation [ 10 , 11 , 12 , 13 ]. The predictors of mortality among adolescents and young adults living with HIV are not uniform across studies [ 7 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zambia is a lower-middle income country in sub-Saharan Africa with relatively high rates of HIV infection, with approximately 12% of the adult population and 1.1% of children currently living with HIV. 25,26 ART became widely available in Zambia in 2005, and a test-and-treat strategy was implemented to attempt to achieve viral suppression in all people living with HIV. However, recent estimates indicate that only about a third of children with HIV in Zambia are virally suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent estimates indicate that only about a third of children with HIV in Zambia are virally suppressed. 25 In the current study, we sought to prospectively ascertain risk factors for new-onset seizures among children with HIV in Zambia. Our primary hypothesis was that early initiation of combination ART and sustained viral suppression would be associated with a reduced risk of seizures.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that there are currently 72 000 Zambian children living with HIV ( 3 ). It was previously reported that 49 000 children living with HIV (CLWHIV) in Zambia do not have access to ART ( 4 ). Although access to ART has undoubtedly reduced mortality, children diagnosed with HIV tend to suffer developmental delays; they are also prone to mental health problems and poor adaptive functioning ( 5 ).…”
Section: Introductionmentioning
confidence: 99%